Persephone in America - Townsend, Alison (Book collections on Project MUSE., 2009)
In Persephone in America, Alison Townsend deftly weaves autobiography with myth in this reinvention of the tale of Demeter and Persephone as seen from the modern woman's perspective. Fraught with emotional honesty, this captivating collection of lyrical and narrative poems chronicles the struggles of the figurative Persephone in three parts-the abduction, descent to the underworld, and return. Townsend turns a shrewd eye to her own experiences, as well as to the lives of other women, to offer an unflinching yet deeply compassionate exploration of such themes as girlhood and.